Prolongation of QT Interval as a Result of Combination Therapy of Oral Artemether-Lumefantrine: A Cross-Sectional Study - Riffat Sultana, Dost Muhammad, Ahmed Ali, Fazal Ur Rehman, Waqar Azim, Muhammad Hashim, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of prolongation of QT interval as a result of combination therapy of oral Artemether-Lumefantrine Study design: A cross-sectional study Place and Duration: This study was conducted at Karachi Institute of Heart Diseases Karachi Pakistan from June 2020 to June 2021. Methodology: The study included a total of 120 participants. Participants were selected by a consecutive sampling method. All the patients were adults and had been diagnosed with malaria by positive blood smear for plasmodium falciparum. The patients had not taken any antimalarial therapy for the last seven days of reporting to the hospital. The treatment was given in six doses of AL combination therapy. The strength of one dose was 80 mg Artemether and 480 mg of Lumefantrine. The QT interval was calculated before and after the therapy administration. Bazett’s formula (Qtc (s) = QT interval / √ RR interval) was used for the calculation of the corrected QT interval (Qtc) Results: The mean age of the patients was 30 ± 2.96 years. A total of 85 (70.83%) were male and 35 (29.17%) were female. According to the age distribution, 31 (25.83%) patients were between the age of 20 years and 30 years. A total of 42 (35%) patients were between the age of 31 and 40 years. 36 (30%) were in the age range of 41 and 50 years. A total of 11 (9.17%) were above the age of 50 years All the patients were analyzed for QT interval prolongation and the QT interval was not prolonged in any of the participants. Conclusion: As QT interval prolongation was not observed in any of the patients, oral AL can be considered a safe combination therapy for the treatment of malaria caused by plasmodium falciparum.